Elder Companion Lesson 5 Home Maintenance and Safety - Elizabeth B. Bolton; Muthusami Kumaran (EDIS, 2015)
An agent's teaching guide for Lesson 5 of the Elder Companion training program. It includes instructions and handouts for a two to three-and-a-half hour lesson in four parts: Part 1: What is Clean? -- Part 2: Organizing for Cleanliness -- Part 3: Managing the Laundry -- Part 4: Safety.